Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm00167
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium

Abstract: Pro.pio.ni.bac.te'ri.um. N.L. n. acidum propionicum propionic aid; L. neut. n. bacterium a small rod; N.L. neut. n. Propionibacterium propionic (acid) bacterium. Actinobacteria / Actinobacteria / Propionibacteriales / Propionibacteriaceae / Propionibacterium Pleomorphic rods , 0.2–1.5 µm ×, 1–5 µm, often diphtheroid or club‐shaped with one end rounded and the other tapered or pointed;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…It has been known for some time that type I strains show variable β-haemolysis activity, which is absent from type II and III strains [34,91]. Although not described in previous proteomic and transcriptomic studies, biochemical analysis has also found that P. acnes produces neuraminidase or sialidase activities that cleave sialoglycoconjugates [92]; several putative genes for the enzyme have been identified within the genome sequence (PPA1560, PPA684, PPA685).…”
Section: Acne Vulgarismentioning
confidence: 99%
“…It has been known for some time that type I strains show variable β-haemolysis activity, which is absent from type II and III strains [34,91]. Although not described in previous proteomic and transcriptomic studies, biochemical analysis has also found that P. acnes produces neuraminidase or sialidase activities that cleave sialoglycoconjugates [92]; several putative genes for the enzyme have been identified within the genome sequence (PPA1560, PPA684, PPA685).…”
Section: Acne Vulgarismentioning
confidence: 99%
“…Bootstrap values of ≥50% are indicated at their respective nodes. Reference type strains are indicated with superscript “†.” The backgrounds of the reference strains are colored according to the sugar (sucrose and/or glucose) utilization capacity of those bacteria based on the data from (1) Lee et al ( 2013 ); (2) Staley ( 1984 ); (3) Kuykendall et al ( 2015 ); (4) Dall'Agnol et al ( 2013 ); (5) Baldani et al ( 2015 ); (6) Hungria et al ( 1993 ); (7) Kuykendall ( 2015 ); (8) Sajnaga and Jach ( 2020 ); (9) Ahnia et al ( 2018 ); (10) Reis et al ( 2004 ); (11) Chen et al ( 2006 ); (12) Coenye et al ( 2001 ); (13) Wolterink et al ( 2005 ); (14) Weon et al ( 2008 ); (15) Qiu et al ( 2017 ); (16) Hardoim et al ( 2013 ); (17) Xu et al ( 2020 ); (18) Ueki et al ( 2006 ); (19) Olsen ( 2015 ); (20) Imhoff ( 2015b ); (21) Diaz-Barrera et al ( 2016 ); (22) Bae et al ( 2006 ); (23) Norris et al ( 2015 ); and (24) Patrick and McDowell ( 2015 ). The black-and-white shading in the columns on the right-hand of the NifH-OTU name indicates the mean relative abundance of the NifH-OTUs in each rice genotype ( n = 2 for Nipponbare; n = 3 for agpl1 , Leafstar, and CG14).…”
Section: Resultsmentioning
confidence: 99%
“…For reference strains used in the phylogenetic trees of 16S rRNA and NifH (Figures 6, 8), the sugar (sucrose and glucose) utilization ability was estimated at the strain, species, and at the genus levels with available information. Most of the reference strains selected for the phylogenetic trees of 16S rRNA and 23) Norris et al (2015); and (24) Patrick and McDowell (2015). The black-and-white shading in the columns on the right-hand of the NifH-OTU name indicates the mean relative abundance of the NifH-OTUs in each rice genotype (n = 2 for Nipponbare; n = 3 for agpl1, Leafstar, and CG14).…”
Section: Sugar Utilization Capacity Of Potential N-fixing Bacteriamentioning
confidence: 99%
“…Propionibacterium freudenreichii, Acidipropionibacterium jensenii , and A. acidipropionici are dairy PAB that are suitable for propionic acid and vitamin B 12 production due to the ability to utilize simple sugars such as glucose and fructose (Patrick & McDowell, 2015; Piwowarek et al., 2018). Nutritional requirements for PAB growth vary with species and strains.…”
Section: Introductionmentioning
confidence: 99%